LOHAS: Marketing a green and sustainable way of living - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2010)
What prompted former corporate warriors like Adam Horler and Tay Lai Hock trade their suits for t-shirts and embrace a new way of life with green and sustainability as its central tenet? It is LOHAS, or Lifestyle of Health and Sustainability, described as a “biggest market you’ve never heard of”. In a recent talk at SMU, Horler and Tay share what is their motivation, what is the appeal of LOHAS, and how are they marketing this concept to bring more converts on board.